Professor of Teaching: The quest for equity and parity - Ragoonaden, Karen (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
Emerging from the contested site of a new university campus, this article reflects on the transformative process of reconceptualizing and rebuilding a professional and an academic stream in a 21st-century Faculty of Education. In order to maximize her own capital, an assistant professor sought tenure in an innovative new stream introduced to her campus, professor of teaching. The novel rank reflected the commitment of the university to provide educational leadership, outstanding teaching, and curriculum innovation to higher education. However, guidelines for promotion to professor were not directive and exhaustive but more suggestive of being situated in place-based environments. Within the context of a market driven and policy-laden post-secondary institution, this was problematic. Since evidence supporting promotion to full professor is dependent on the discipline and the faculty, a myriad of interpretations of what exactly constituted a professor of teaching emerged. Based on the ambiguity of these policies, the discussion surrounding the experiences of otherness and marginalization which arose as this scholar-practitioner focused on her work as a teacher educator and a researcher in an emerging rank became of singular interest.